Les avant-gardes et la narration - Tania Collani (Cahiers de Narratologie)
The European Avant-gardes of the first half of the 20th century held a strangely homogeneous (though often accidental) discourse on the novel : on a theoretical level, the Futurists, the Dadaists and the Surrealists were resolutely against a literary form which embodied the bourgeois spirit of the 19th century. Nonetheless, these same avant-garde authors wrote several novels. This is not only another paradox of modernity, but rather a stance on the part of such writers which needs to be investigated. The paper offers a view of the formal constraints which inspired avant-gardes’ prosaic production, as well as an analysis of a corpus of texts in prose often neglected because of their “hermetism”, which brings them nearer to poetry than to novel.